A dynamic ocean wave simulator based on six-degrees of freedom parallel platform. (October 2018) - Chuan, Wu; Huafeng, Ding; Lei, Han
The development of marine equipment is an international trend. It is also a strategic choice for coastal countries, as the basis to construct a strong marine power. For this purpose, the Chinese government has strengthened the support for marine equipment research and development in recent years. For most researchers, however, they cannot test their marine equipment at an actual ocean site due to limited fund as well as because the devices are not easy to move. Hence, devices for simulating ocean waves are emerging on this basis. But these existing devices are not able to completely recreate the motion of an ocean wave. For this reason, this paper introduces a dynamic ocean wave simulator that is based on six-degrees of freedom parallel platform. The simulator consists of two components: a boat model placed on the sea and a six-degrees of freedom platform kept in a room. The boat is used to collect data of the ocean wave motion, and the data are simultaneously transferred, via a general packet radio service wireless network to a controller equipped on the platform. The controller will make calculation of the data and then control the platform to perform motions accordingly, whereby the ocean wave motion can be recreated. After being designed, the simulator is tested in the lab. The results show that the simulator can simulate simple ocean waves and satisfies the requirements of ordinary marine projects.